Antimicrobial activity of sodium hypochlorite associated with intracanal medication for Candida albicans and Enterococcus faecalis inoculated in root canals - Marcia Carneiro Valera; Katy Costa Godinho da Silva; Lilian Eiko Maekawa; Cláudio Antonio Talge Carvalho; Cristiane Yumi Koga-Ito; Carlos Henrique Ribeiro Camargo; Raphael Silva e Lima (University of São Paulo, 2009)
OBJECTIVE: The purpose of this study was to evaluate the action of sodium hypochlorite (NaOCl) associated with an intracanal medication against Candida albicans and Enterococcus faecalis inoculated in root canals. MATERIAL AND METHODS: Thirty-six human single-rooted teeth with single root canals were used. The canals were contaminated with C. albicans and E. faecalis for 21 days and were then instrumented with 1% NaOCl. The roots were divided into 3 groups (n=12) according to the intracanal medication applied: calcium hydroxide paste, 2% chlorhexidine (CHX) gel, and 2% CHX gel associated with calcium hydroxide. The following collections were made from the root canals: a) initial sample (IS): 21 days after contamination (control), b) S1: after instrumentation, c) S2: 14 days after intracanal medication placement; S3: 7 days after intracanal medication removal. The results were analyzed statistically by the Kruskal-Wallis test at 5% significance level. RESULTS AND CONCLUSIONS: Both 1% NaOCl irrigation and the intracanal medications were effective in eliminating E. faecalis and C. albicans inoculated in root canals.